The Concept of Kafa’ah in the Nineteenth Century Javanese Muslim Scholars’ View: A Study on the Ulama Rifi’yah’s Thought - Sidqi, Imaro; Rasidin, Mhd. (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2023)
This study aims to analyze the views of the Rifa’iyah scholars in Kandeman District, Batang Regency, regarding the concept of kafa’ah in marriage, as well as to know and understand the factors behind the concept of kafa’ah that they constructed. This juridical-sociological research used a historical-sociological approach. The results showed that in the views of the Rifa’iyah scholars in Kandeman District, Batang Regency, towards the concept of kafa’ah, which is interpreted as equal or balanced, Rifa’iyah scholars in the area understand that the urgency function of kafa’ah lies in creating a harmonious family even though kafa’ ah does not determine whether or not a marriage is valid. According to Ulama Rifa’iyah, the essential criterion for kafa’ah must be of the same religion. Then, the scholars provide recommendations following the formation of the kafa’ah conception contained in the Tabyinal al-Islah Book that a prospective wife must be of a lower degree than a prospective husband so that a wife respects/obeys her husband. However, if the context is the other way around, it is not a problem as long as the wife obeys her husband. The concept of kafa’ah, formed among the Rifa’iyah scholars in Kandeman District, Batang Regency, was caused by various factors, including religion, beauty, lineage, and wealth. There are supporting factors, namely educational, social and cultural factors